Ensuring respect for indigenous cultures: A moral rights approach - Brigitte Vézina (Centre for International Governance Innovation (CIGI), 2020)
From commercials to movies to fashion, Indigenous artworks have been misused in ways that are offensive to the artists who created them and disrespectful of the cultures that inspired them. Using Indigenous traditional cultural expressions (TCEs) without acknowledging their sources or providing financial compensation to the artists undermines the TCEs' traditional value and amounts to cultural theft. This paper looks at protecting TCEs using copyright's moral rights approach, which provides intellectual property protection based on acknowledgement, respect and integrity.
Keywords: 330; Cultural Identity; Intellectual Property Rights; Indigenous Peoples; Kulturelle Identität; Immaterialgüterrechte; Indigene Völker